Persepsi Konsumen Terkait Iklan #Skinsolver Serum Somethinc Terhadap Keputusan Pembelian Produk Di Kalangan Gen Z - Fathiya, Ratu Aisya Farah; Ramdani, Guruh (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the influence of consumer perception toward the #SkinSolver Serum Somethinc advertisement on purchase decisions among Generation Z in Jakarta. In the digital era, marketing strategies increasingly utilize visually engaging content and emotionally resonant messaging to attract younger audiences. The #SkinSolver advertisement, with its aesthetic visuals, informative narrative, and strong brand presence, is perceived to shape consumer attitudes and influence their purchasing behavior effectively. This research employs a quantitative descriptive approach through a survey distributed to 100 Gen Z respondents exposed to the advertisement. The results indicate that consumer perception, particularly concerning information quality, visual appeal, and brand image—has a positive and significant effect on purchase decisions. These findings highlight the importance of aligning advertising content with audience preferences to enhance the persuasive power of digital marketing campaigns.